PARADIGMA PENDIDIKAN DEMOKRASI DAN PENDIDIKAN ISLAM DALAM MENGHADAPI TANTANGAN GLOBALISASI DI INDONESIA - Ali Miftakhu Rosyad; Muhammad Anas Maarif (Nazhruna: Jurnal Pendidikan Islam, 2020)
The study aims to explore the paradigm of Islamic education, democratic education to face the globalization challenges in Indonesia. This research method was a qualitative approach with type of literature study. Paradigmatically, democratic education is the process to develop all human potentials that values of plurarity and heterogeneity as a consequence of cultural, ethnic, ethnic, and religious diversity. The emphasized main values in democratic education are equality and tolerance. Whereas in Islamic education, the values of transcendence taught in the curriculum must be practiced in daily life in order to achieve the pious charity conference. The challenges of globalization that have penetrated into the world of education have become a driving force for inclusive and sustainable educational innovation.This study is expected to provide contributions for academician, education practical, and teacher in Indonesia as an actualization of Islamic education and democratic education to confront globalization challenges in Indonesia.